Exploring rating scale functioning for survey research - Wind, Stefanie A. (Anne) (Los Angeles : SAGE, 2023)
"Items with ordered response categories are common in survey research, such as when respondents are asked how much they agree with certain statements (1=strongly agree to 5=strongly disagree). But how large are the differences between categories of response, and how well do they distinguish between respondents? This volume is the first to introduce the evaluation of rating scales to an audience of survey researchers. Evaluating Rating Scale Functioning for Survey Research provides researchers with an overview of rating scale analysis along with practical guidance on how to conduct such analyses with their own survey data. Author Stefanie A. Wind presents three categories of methods: Rasch models; non-Rasch Item Response Theory (IRT) models; and non-parametric models, together with practical examples. Tutorials, datasets, and software code (R and Facets) to accompany the book are available on the book's website"--
Includes bibliographical references and index.
Keywords: Psychometrics; Invariant measures; Rasch models; Psychology -- Statistical methods; Social sciences -- Statistical methods; Social surveys